La villa romaine de Montcaret. Une villa et son environnement dans le sud-ouest de la Gaule - Berthault, Frédéric (DAN@, 2021)
The archeological site of Montcaret consists of the Pars urbana of a large Roman implantation. It is composed of two levels (Early and late roman Empires), themselves divided into several periods. The last period (5th century A.D.) offers the largest basilica room in the region, a triclinium, a pool and some very well preserved mosaics. The site is inhabited again in the Middle Ages, with a Romanesque church and a necropolis. The site has been studied in its diachronic and synchronic context and the Pars agraria close to the estate has deserved a special research. The artifacts found in the excavations (Roman and medieval coins, Roman and medieval, ceramics, architectural fragments, reliquary cross, sarcophagi, perinatal burials) have been the subject of specific studies, each of them carried out by specialists. They are presented in the museum space of the site which can be visited.